Immediate analgesic effect of two modes of transcutaneous electrical nerve stimulation on patients with chronic low back pain: a randomized controlled trial - Pivovarsky,Madeline Luiza Ferreira (2021)
ABSTRACT Objective To compare and assess the immediate analgesic effects of conventional and burst transcutaneous electrical nerve stimulation in patients with chronic low back pain. Methods We conducted a three-arm single-blinded randomized controlled trial. A total of 105 patients with non-specific chronic low back pain aged between 18 and 85 years were randomly assigned into the following groups: Placebo Group (sham electrical stimulation), Conventional TENS Group (continuous stimulation at 100Hz for 100µs with sensory intensity), and Burst TENS Group (stimulation at 100Hz modulated at 2Hz for 100µs with motor-level intensity). All groups received a single application of transcutaneous electrical nerve stimulation for 30 minutes. The outcomes, namely, pain intensity, quality of pain, and pressure pain threshold were measured by the visual analog scale, McGill pain questionnaire, and algometry, respectively. The patients were evaluated before and immediately after the transcutaneous electrical nerve stimulation application. Results Pain intensity (visual analog scale score) and quality of pain (McGill pain questionnaire score) significantly decreased (p<0.05) in Intervention Groups (Conventional TENS Group and Burst TENS Group). A positive effect was observed in the interventions compared to the Placebo Group in all domains of the McGill pain questionnaire (p<0.05), excepting for the pain intensity. Pressure pain threshold significantly increased (p<0.05) immediately after the transcutaneous electrical nerve stimulation application in both Intervention Groups, but not in the Placebo Group. For significant difference was found during assessment when comparing both Intervetion Group. Conclusion Both transcutaneous electrical nerve stimulation modes were effective for pain modulation. Moreover, there was an increase in the pressure pain threshold. No significant results were found to indicate the best mode for the treatment of chronic low back pain. Clinical Trial Registration: RBR-59YGRB.